Impact of Enhanced Recovery After Surgery on Postoperative Recovery for Pancreaticoduodenectomy: Pooled Analysis of Observational Study - Cao, Yang; Gu, Hui-Yun; Huang, Zhen-Dong; Wu, Ya-Peng; Zhang, Qiong; Luo, Jie; Zhang, Chao; Fu, Yan (Frontiers in Oncology, 2019)
Purpose: To assess the impact of enhanced recovery after surgery (ERAS) protocols in pancreaticoduodenectomy. Methods: Four databases were searched for studies describing ERAS program in patients undergoing pancreatic surgery published up to May 01, 2018. Primary outcomes were mortality, readmission, reoperation and postoperative complications. Secondary outcomes were the length of stay and cost. Results: A total of 19 studies met inclusion and exclusion criteria and included 3,387 patients. Meta-analysis showed a decrease in pancreatic fistula (OR=0.79, 95% CI: 0.67 to 0.95; I2=0%), infection (OR=0.63, 95% CI: 0.50 to 0.78; I2=0%), especially incision infection (OR=0.62, 95% CI: 0.42 to 0.91; I2=0%) and pulmonary infection (OR=0.28, 95% CI: 0.12 to 0.66; I2=0%). Length-of-stay (MD: -3.89 days, 95% CI: -4.98 to -2.81; I2=78%) and cost were also significantly reduced. There was no significant increase in mortality, readmission, reoperation, or delayed gastric emptying. Conclusion: This analysis revealed that using ERAS protocols in pancreatic resections may help decrease the incidence of pancreatic fistula and infections. Furthermore, ERAS also reduces length of stay and cost of care. This study provides evidence for the benefit of ERAS protocols.